The Role Of Notary In The Making Of Franchise Agreements Toward The Business Actors In Order To Get Legal Protection Guarantee - Eliani Safitri; Justisia Pamilia Luberty; Aryani Witasari (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
Franchising is essentially a marketing concept in order to expand a business network quickly. Franchising is not an alternative, but one way that is as strong and strategic as the conventional way of developing a business. In a franchise agreement, the role of a notary is required even though the franchise agreement itself is a standard agreement without a notary. However, in order to make the deed of the agreement is more authentic, the role of a notary is necessary to ensure the legal protection. The research method used was normative juridical. Normative legal research is a legal research conducted by reviewing materials derived from various laws and other materials from various literatures. Based on the results of research and discussion, it can be concluded that the role of Notary is important in making the deed of the franchise agreement in addition to preventing the occurrence of misappropriation (negligence or default) of one party. The notary also ensures the legal protection of the deed of the agreement because it is made under the legal protection. The franchise is an engagement or agreement between two parties in which all provisions refer to Article 1313 of the Civil Code of the treaty, article 1320 of the Civil Code of the validity of the agreement and Article 1338 paragraph (1) of the Civil Code on the principle of freedom of contract.Keywords: Notary; Franchise; Legal Protection.